2021
DOI: 10.1038/s41433-021-01487-0
|View full text |Cite
|
Sign up to set email alerts
|

Fluid as a critical biomarker in neovascular age-related macular degeneration management: literature review and consensus recommendations

Abstract: Current guidelines on the management of patients with neovascular age-related macular degeneration (nAMD) lack clear recommendations on the interpretation of fluid as seen on optical coherence tomography (OCT) imaging and the incorporation of this information into an ongoing disease treatment strategy. Our objective was to review current guidelines and scientific evidence on the role of fluid as a biomarker in the management of nAMD, and develop a clinically oriented, practical algorithm for diagnosis and mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(82 citation statements)
references
References 81 publications
0
82
0
Order By: Relevance
“…Fluid-based prognostication is one of the current major issues in the field of neovascular AMD. 13 In particular, intraretinal fluid is a well-known biomarker that is associated with poor visual outcome. 13,25 Because the location of BALAD is "intraretinal," BA-LAD can be considered as the presence of "intraretinal fluid."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluid-based prognostication is one of the current major issues in the field of neovascular AMD. 13 In particular, intraretinal fluid is a well-known biomarker that is associated with poor visual outcome. 13,25 Because the location of BALAD is "intraretinal," BA-LAD can be considered as the presence of "intraretinal fluid."…”
Section: Discussionmentioning
confidence: 99%
“…12 Although anti-VEGF therapy markedly improves the treatment outcome of neovascular AMD, there is no modality to completely "cure" the disease. Because imaging biomarkers are used as an essential index in treating neovascular AMD, 13 investigating potential biomarkers in neovascular AMD would be of great value. To date, only a paucity of knowledge is available regarding the characteristics and clinical features of BALAD in neovascular AMD.…”
mentioning
confidence: 99%
“…In clinical trials and routine clinical practice, assessments of treatment efficacy and decisions to re-treat or extend the treatment interval in T&E regimens are typically based on changes in anatomic endpoints such as central retinal thickness (CRT), as assessed by optical coherence tomography (OCT) [ 2 , 6 , 7 ]. Recently, there has been growing interest in exploring how fluid localization in different compartments may offer superior prognostic value to that of CRT in elucidating the relationship between visual outcomes, intraretinal fluid (IRF), and subretinal fluid (SRF) [ 6 9 ]. However, to date, most analyses of the relationships between retinal fluid status and visual acuity in the management of nAMD have been based on fixed-dose and PRN regimens [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results were observed The presence of central SRF, rather than central IRF, was the most common parameter leading to hypothetical switch criteria being met at both week 8 and week 24. We did not define hypothetical switch criteria according to the presence of central IRF only since few guidelines distinguish between the types of fluid when providing recommendations, with the same retreatment approach generally recommended regardless of the type and location of fluid observed [17]. This is interesting given that studies have shown what appears to be an important difference in the relationship between BCVA and either IRF or SRF [18].…”
Section: Discussionmentioning
confidence: 99%